The Comparıson Of The Cephalometrıc Measurements Of Chıldren And Adult Indıvıduals - Erdal Deniz; Ümit Gazilerli (Galenos Yayinevi, 1990)
This study was carried out on 100 cephalometric head films obtained from 50 children (25 girls and 25 boys) and 50 adult individuals (25 females and 25 males). Some cephalometric angles and distances were measured. The measurements were compared by the "Student t" test in order to determine whether there were any differences between sexes and between chidren and adults. At some measurements, important differences were found between the sexes and between the children and the adults. Altough some differences were also found in the angular measurements they were not evident as much as those in linear measurements. As a conclusion, the angular measurements may be more reliable than linear measurements in diagnosis and treatment planning. However, when the linear measurement is used, the sex and the growth factor must be taken into consideration.